IL-37 Gene Modification Enhances the Protective Effects of Mesenchymal Stromal Cells on Intestinal Ischemia Reperfusion Injury - Dejun Kong; Yonghao Hu; Xiang Li; Dingding Yu; Hongyue Li; Yiming Zhao; Yafei Qin; Wang Jin; Baoren Zhang; Bo Wang; Hongda Wang; Guangming Li; et al. (Hindawi Limited, 2020)
Background. Ischemia reperfusion injury (IRI) is the major cause of intestinal damage in clinic. Although either mesenchymal stromal cells (MSCs) or interleukin 37 (IL-37) shows some beneficial roles to ameliorate IRI, their effects are limited. In this study, the preventative effects of IL-37 gene-modified MSCs (IL-37-MSCs) on intestinal IRI are investigated. Methods. Intestinal IRI model was established by occluding the superior mesenteric artery for 30 minutes and then reperfused for 72 hours in rats. Forty adult male Sprague-Dawley rats were randomly divided into the sham control, IL-37-MSC-treated, MSC-treated, recombinant IL-37- (rIL-37-) treated, and untreated groups. Intestinal damage was assessed by H&E staining. The levels of gut barrier function factors (diamine oxidase and D-Lactate) and inflammation cytokine IL-1β were assayed using ELISA. The synthesis of tissue damage-related NLRP3 inflammasome and downstream cascade reactions including cleaved caspase-1, IL-1β, and IL-18 was detected by western blot. The mRNA levels of proinflammatory mediators IL-6 and TNF-α, which are downstream of IL-1β and IL-18, were determined by qPCR. Data were analyzed by one-way analysis of variance (ANOVA) after the normality test and followed by post hoc analysis with the least significant difference (LSD) test. Results. IL-37-MSCs were able to migrate to the damaged tissue and significantly inhibit intestinal IRI. As compared with MSCs or the rIL-37 monotherapy group, IL-37-MSC treatment both improved gut barrier function and decreased local and systemic inflammation cytokine IL-1β level in IRI rats. In addition, tissue damage-related NLRP3 and downstream targets (cleaved caspase-1, IL-1β, and IL-18) were significantly decreased in IRI rats treated with IL-37-MSCs. Furthermore, IL-1β- and IL-18-related proinflammatory mediator IL-6 and TNF-α mRNA expressions were all significantly decreased in IRI rats treated with IL-37-MSCs. Conclusion. The results suggest that IL-37 gene modification significantly enhances the protective effects of MSCs against intestinal IRI. In addition, NLRP3-related signaling pathways could be associated with IL-37-MSC-mediated protection.